A STUDY ON E-GOVERNANCE IN BELAGAVI DISTRICT ADMINISTRATION - Dr. M.N. Ramesh; Dr. Mallikarjun P. Shegunshi (Elementary Education Online, 2023)
Electronic Governance in India is a newly settled perception. The introduction of National Satellite based Computer Network (NICENET) in 1987 and following promotion of District Information of the National Informatics Center (DISNIC) program to computerize all district offices in the nation for which free software and hardware was accessible to the state Governments provided the essential incentive for e-Governance. Electronic Governance thereafter advanced with the development of technology